Lenalidomide‐based response‐adapted therapy for older adults without high risk myeloma. (12th December 2018) - Baz, Rachid; Naqvi, Syeda Mahrukh Hussnain; Lee, Jae‐Hoon; Brayer, Jason; Hillgruber, Nancy; Fridley, Brooke L.; Shain, Kenneth H.; Sullivan, Daniel M.; Alsina, Melissa
Summary: Combined lenalidomide and dexamethasone is a standard‐of‐care therapy for the treatment of older adults with multiple myeloma. Lenalidomide monotherapy has not been evaluated in newly diagnosed myeloma patients. We conducted a phase II study, evaluating a response‐adapted therapy for older adults newly diagnosed with multiple myeloma without high‐risk features who were ineligible for high‐dose therapy and stem cell transplant. Patients were started on single‐agent lenalidomide, and low‐dose dexamethasone was added in the event of progressive disease, in a response‐adapted approach. The primary endpoint was progression‐free survival (PFS), and the International Myeloma Working Group's uniform response criteria were used to assess response and progression. Twenty‐seven patients were enrolled, and 20 (74%) experienced a partial response or better to this response‐adapted therapy. After a median follow‐up of 69 months, the median PFS was 36 months [95% confidence interval (CI), 29·8 to not reached], and the median overall survival was 65 months (95% CI, 35·3 to not reached). Grade 3/4 adverse events were mainly haematological in nature. This response‐adapted therapy in this patient population is feasible and results in durable responses that compare favourably with concurrent lenalidomide and dexamethasone. These results should be validated in prospective studies.